FAKTOR DETERMINAN KEJADIAN STUNTING PADA ANAK SEKOLAH DAN PENGARUHNYA TERHADAP PRESTASI BELAJAR DI SDN 09 NANGGALO KOTA PADANG TAHUN 2017 - Dezi Ilham; Wilda Laila (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Prevalence of stunting among school-age children around the world (5-14 years) is about 28% (171 million children), nationally 30.7%, while for West Sumatra 26.6% and Padang City is 37.1%. The prevalence of stunting from the results of screening conducted in grade I elementary school students in Padang was 5.14%, the highest prevalence was in SDN 09 Nanggalo by 30%.The purpose of this study to determine the determinant factors of stunting events in school children and its effect on learning achievement at SDN 09 Nanggalo Padang City in 2017. This research use Cross Sectional Study design, total of 332 children and sample 75 children. The statistical test used is chi- square on p-value <0.05. From the result of research of stunting student prevalence counted 16%, less half of students with low learning achievement (44%), determinant factor of stunting event is mother education, mother knowledge and energy consumption and protein and there is stunting effect to learning achievement. It is recommended to nutrition officers to regularly measure school children's height and weight to monitor the nutritional status of school children and teachers and principals to provide more activities that can improve learning achievement, such as holding additional lessons.